Specific Protein 1 and p53 Interplay Modulates the Expression of the KCTD-Containing Cullin3 Adaptor Suppressor of Hedgehog 2 - Angrisani, Annapaola; Di Fiore, Annamaria; Di Trani, Claudia Augusta; Fonte, Simone; Petroni, Marialaura; Lospinoso Severini, Ludovica; Bordin, Fabio; Belloni, Laura; Ferretti, Elisabetta; Canettieri, Gianluca; Moretti, Marta; De Smaele, Enrico (Frontiers in Cell and Developmental Biology, 2021)
The Hedgehog (Hh) signaling pathway plays a crucial role in normal embryonic development and adult tissue homeostasis. On the other end, dysregulated Hh signaling triggers a prolonged mitogenic response that may prompt abnormal cell proliferation, favoring tumorigenesis. Indeed, about 30% of medulloblastomas (MBs), the most common malignant childhood cerebellar tumors, exhibits improper activation of Hh signaling. The oncosuppressor KCASH2 has been described as a suppressor of the Hh signalling pathway, and low KCASH2 expression was observed in Hh-dependent MB tumor. Therefore, study of the modulation of KCASH2 expression may provide fundamental information for the development of new therapeutic approaches, aimed to restore physiological KCASH2 levels and Hh inhibition. To this end, we have analyzed the TATA-less KCASH2 proximal promoter and identified key transcriptional regulators of this gene: Sp1, a TF frequently overexpressed in tumors, and the tumor suppressor p53. Here, we show that in WT cells Sp1 binds KCASH2 promoter on several putative binding sites, leading to increase of KCASH2 expression. On the other hand, p53 is involved in negative regulation of KCASH2. In this context, the balance between p53 and Sp1 expression, and the interplay between these two proteins determines whether Sp1 acts as activator or repressor of KCASH2 transcription. Indeed, in p53-/- MEF and p53 mutated tumor cells, we hypothesize that Sp1 drives promoter methylation through increased expression of the DNA Methyltransferase 1 (DNMT1) and reduces KCASH2 transcription, which can be reversed by Sp1 inhibition or use of demethylating agents. We suggest therefore that downregulation of KCASH2 expression in tumors could be mediated by gain of Sp1 activity and epigenetic silencing events in cells were p53 functionality is lost. This work may open new venues for novel therapeutic multidrug approaches in the treatment of Hh-dependent tumors carrying p53 deficiency.